Partnership through co-creation: Lessons learnt at the University of Adelaide - Snelling, Catherine Anne; Loveys, Beth R; Karanicolas, Sophie; Schofield, Nathan James; Carlson-Jones, William; Weissgerber, Joanne; Edmonds, Ruby; Ngu, Jenny (International Journal for Students as Partners, 2019)
This paper describes three exemplars of practice inspired by emerging evidence that student-staff partnerships have the potential to significantly enhance many areas of higher education. Students and academics at the University of Adelaide have successfully implemented this collaborative approach across a range of learning and teaching contexts. The Design Thinking Framework, developed by the Hasso Plattner Institute of Design at Stanford University, was utilised at a faculty, program, and course level to frame each of the exemplars, due to its implicit approach to creativity, collaborative development, and achievement of solutions. The iterative nature of the framework facilitated a review cycle for continuous improvement in each Students-as-Partners’ initiative. Analysing the outcomes of each exemplar has identified common hallmarks of successful partnership, and these indicators have the potential to contribute to the growing body of evidence that defines best practice in this pedagogy